On ‘Economies of Sequence’ in the Architectural Theory of Agglomeration: A Case of the Kyoto Tourism Industry - Akifumi Kuchiki (Economies, 2020)
This paper focuses on an architecture-based theory of agglomeration. An agglomeration is composed of a number of segments such as physical infrastructure facilitation including airports and stations. ‘Economies of sequence’ can be defined as the sequencing of the segments toward the efficient building of an agglomeration. The main three findings are as follows: first, foreign nationals from Kansai International Airport Granger-cause the number of tourists to Kyoto Prefecture, foreign nationals from Kansai International Airport Granger-cause the number of foreign tourists to Kyoto City, and passengers at JR Kyoto Station Granger-cause the number of tourists to Kyoto City; second, the number of foreign tourists Granger-causes revenues in the tourism industry in the cases of Malaysia, the United States of America, and China; and third, the promotion of the tourism industry to redevelop Kyoto station mall in 1997, the “Kyoto Winter Special” campaign in 2003, and the global “Travel & Leisure” destination SNS (social networking service) promotion in 2015 were effective in building the segments of a tourist agglomeration. In conclusion, the economies of sequence of the segments of a tourism industry agglomeration are as follows: the first priority is to reduce transportation costs for tourists through the renovation of airports and stations, and the next segments for enhancing the level of cultural elements are a branding strategy through the promotion of the tourist industry by campaigns and projects using social network systems.